Rescue Radioguided Laparoscopy Surgery for Meckel's Diverticulum. Issue 25 (June 2015) - Deus, Javier; Millera, Alfonso; Andrés, Alejandro; Prats, Enrique; Suarez, Manuel; Gil, Ismael; Salcini, José Luis; Lahoz, Manuel; De Gregorio, Miguel Angel; Kapritsou., Maria
<x xml:space="preserve">Abstract</x> Abstract The extirpation of Meckel's diverticulum (MD) via conventional or laparoscopic surgery is the definitive treatment. However, certain circumstances may modify or alter this situation and require the application of exceptional measures. We report a case under our observation who previously had an exploratory abdominal laparotomy for a suspected MD; however, the findings were negative. At that time, the diagnosis was established based on low-level gastrointestinal bleeding and isotopic tests that confirmed the existence of the diverticulum. Given the findings of gamma-graphic exploration and the previous negative surgical exploration, a decision was made to remove the lesion by laparoscopic radioguided surgery. The patient underwent bilateral laparoscopic radioguided surgery using a gamma radiation detection probe. The exploration of the abdominal cavity noted the existence of the diverticulum about 60 to 70 cm from the ileocecal valve. In this way, it was possible to proceed with the resection of the bowel loop and perform an intracorporeal anastomosis termino lateral. The postoperative course was uneventful, and the patient was discharged on the fifth postoperative day. We believe that the combination of radioguided surgery and single photon emission computed tomography/computed tomography could be useful for treating lesions in locations that are surgically difficult because of the characteristics of the lesion itself or the peculiarities of an individual patient.